2010
DOI: 10.1073/pnas.0914031107
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating nanowire devices on diverse substrates by simple transfer-printing methods

Abstract: The fabrication of nanowire (NW) devices on diverse substrates is necessary for applications such as flexible electronics, conformable sensors, and transparent solar cells. Although NWs have been fabricated on plastic and glass by lithographic methods, the choice of device substrates is severely limited by the lithographic process temperature and substrate properties. Here we report three new transfer-printing methods for fabricating NW devices on diverse substrates including polydimethylsiloxane, Petri dishes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
109
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 40 publications
3
109
0
Order By: Relevance
“…Compression of elastic layers can also be found in microfabrication. For instance, elastomeric stamps are widely used in the transfer-printing of nanowires (Lee et al, 2010), nanoribbons (Khang et al, 2006) and nanomembranes (Kim et al, 2008) due to their moldability and appropriate surface adhesion. When the stamp is compressed between a rigid backing layer and the nanomaterials on a rigid donor wafer, the deformation of the stamp and the shear stress on the stamp-nanomaterial interface will dictate the quality of the transfer-printing, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Compression of elastic layers can also be found in microfabrication. For instance, elastomeric stamps are widely used in the transfer-printing of nanowires (Lee et al, 2010), nanoribbons (Khang et al, 2006) and nanomembranes (Kim et al, 2008) due to their moldability and appropriate surface adhesion. When the stamp is compressed between a rigid backing layer and the nanomaterials on a rigid donor wafer, the deformation of the stamp and the shear stress on the stamp-nanomaterial interface will dictate the quality of the transfer-printing, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The semiconductor nanowire elements can display multiple sensory functionalities, including photon (24), chemical, biochemical, and potentiometric (17,22) as well as strain (25,26) detection, which make them particularly attractive for preparing hybrid active materials as described below. We have first characterized photoconductivity changes (i.e., photon detection) of nanowire elements while imaging the nanoelectronic networks with a confocal microscope by recording conductance as a function of xyz coordinates and overlapping with simultaneously acquired fluorescence images (Materials and Methods; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that Si nanowires have a high piezoresistance response (25), making them good candidates for strain sensors (26). To explore the potential of Si nanowire device arrays to map strain within materials, we have prepared and characterized 3D macroporous nanoelectronic network/elastomer hybrid materials (Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…TRT is a kind of thin, flexible and roll‐to‐roll compatible tape, which shows large, switchable and irreversible change in adhesion strength when it is heated to around 100 °C. Although several successful applications of TRT in transferring monolayer 2D materials (e.g., graphene55, 56, 57 or MoS 2 58), ink,59 and silicon60 have been demonstrated by controlling adhesion strength of TRT via varying the temperature, the principle of thermal release transfer printing with TRT has not been discussed in details. In this study, the mechanism of this approach is analyzed by studying the peeling velocity and temperature dependence of energy release rate with experiments and fracture‐mechanics models.…”
Section: Introductionmentioning
confidence: 99%